Optimizing Arabic Language Learning at MAN 1 Ponorogo Through the Flipped Classroom Approach - Ratna Utami Nur Ajizah; Fahmi Aulia Zaki Romdhoni (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2024)
The aim of this study is to find out how using a flipped classroom approach can help students at MAN 1 Ponorogo learn Arabic better. The study uses a qualitative approach to case studies. Data is collected through in-depth interviews with teachers and students, observations in the classroom, and analysis of related documents. Thematic analysis is used to find the main patterns and themes. Study results show that a flipped classroom approach can improve student interaction and participation in Arabic learning. Students are more active in class discussion and are better prepared to take lessons after studying the material independently at home. The teacher also said that students were more confident and motivated to use Arabic. The study found that the flipped classroom approach could be used effectively to teach Arabic at MAN 1 Ponorogo. This method not only improves students' understanding and skills, but also increases their desire to participate actively in learning.